The effects of culture on planning and technology in the internationalisation of Medellín's SMEs (2014)
As an emerging market, global business is of greatest importance in Colombia and several efforts are implemented to keep up with the international competitive environment. However, these efforts should be accompanied with the development of entrepreneurial capabilities in a wide range of ambits, among others, cross-cultural management. This chapter describes cultural influences in internationalisation activities of Medellin's small and medium enterprises based on original research results using descriptive multi-case methods within five companies and documentary review of business publications. It starts with an overview of the Colombian SME and cross-cultural management theories; then, the cultural influences on planning and internationalisation are listed, suggesting that systematic plans during internationalisation are not followed and technology tools are not properly seized due to management styles, a changing business environment, and small education levels. ï¿½ 2014 by IGI Global. All rights reserved.